The Effect Of Giving Rewards On Student Motivation In Islamic Religious Education Subjects - Saifuddin Saifuddin; Diaya Uddeen Deab Mahmoud Alzitawi; Siti Syariifatul Lathiifah (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2023)
In the learning process, educators often get into trouble when students feel sleepy, bored, lazy, and lack enthusiasm so they are less active in the learning process. The reward method is an effort to foster student learning motivation. The research aims to examine the effect of rewards on students' learning motivation in Islamic Religious Education. The research design used was experimental in two classes, namely class X MPK as the control class and class X PMS as the experimental class—data collection by questionnaire, observation, and documentation. The data obtained were analyzed using parametric analysis, namely the Independent sample T-Test. The results of the research show that reward affects students' learning motivation. Students who are given rewards in the learning process have an average value of learning motivation higher than the class that is not given reward treatment. The average student motivation after being given a reward is 76.47. While in the class I was not given an average bonus of 47.07. Keywords: Giving Rewards, Learning Motivation, Islamic Religious Education.